PROBLEMATIKA PROGRAM ZERO WASTE DI SMAN 1 BATUKLIANG - FITRIANI, NOVA; MUSTARI, MOHAMAD; SAWALUDIN, SAWALUDIN; SUMARDI, LALU (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
One of the roles of the government in reducing waste in Indonesia is through the implementation of the zero-waste program. The implementation of the zero-waste concept in schools involves education about the environment, waste reduction, waste sorting, recycling, and the use of environmentally friendly products. The aim of this research is to understand the implementation, problems, and solutions of the zero waste program at SMAN 1 Batukliang. This research uses a qualitative research method with a case study approach, and data is collected through interviews, observations, and documentation. Data analysis is then conducted through data reduction, data presentation, and drawing conclusions. The results show that the implementation of the zero-waste program at SMAN 1 Batukliang is considered to have achieved its objectives and has had a positive impact on the school and its surroundings. However, there are challenges encountered during the program, such as misunderstandings between the members of the Student Council (OSIS) and some waste pickers around the school, as well as some students who are less actively participating in the program. Therefore, solutions to these issues have been formulated, such as coordinating with waste pickers through teacher assistance and conducting seminars or socialization activities to enhance student understanding. ABSTRAKSalah satu peran pemerintah dalam pengurangan sampah yang ada di Indonesia yaitu dengan penerapan program zero waste. Penerapan konsep zero waste di sekolah melibatkan pendidikan tentang lingkungan, pengurangan sampah, pemilahan sampah, daur ulang, dan penggunaan barang ramah lingkungan. Tujuan dari penelitian ini yaitu untuk mengetahui bagaimana pelaksanaan, problematika, dan solusi dari program zero waste di SMAN 1 Batukliang. Penelitian ini menggunakan metode penelitian kualitatif dengan jenis penelitian studi kasus, data penelitian diambil melalui wawancara, observasi, dan dokumentasi. kemudian analisis data dilakukan dengan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa pelaksanaan program zero waste di SMAN 1 Batukliang dianggap telah berjalan sesuai tujuan dan memberikan dampak positif bagi lingkungan sekolah dan sekitarnya, dibalik itu terdapat problematika yang terjadi selama program zero waste ini yakni ketidaksepahaman antara anggota OSIS dan beberapa pemulung disekitar sekolah, serta masih ada sebagian siswa yang kurang berpartisipasi aktif dalam program. Sehingga terbentuklah solusi dari hal tersebut seperti melakukan koordinasi dengan pemulung melalui bantuan guru, dan diadakannya penyuluhan atau sosialisasi untuk meningkatkan pemahaman siswa.